Wykorzystanie nowoczesnych technologii w doskonaleniu procesów controllingowych - Chomiak-Orsa, Iwona (The Use of Information Technology in Controlling Systems Advancement, 2007)
The aim of this article is to present the essence and the importance of controlling information system. The paper also categorizes the software applications, which support controlling system in organization. To effectively manage the controlling processes, managers need to analyze data collected from different sources and transformation it. Information technology generates many solutions in this way. Business Intelligence becomes part of the standard information technology, used by more and more business organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 95-104